Novel triangular auxetic honeycombs with enhanced stiffness. (1st December 2021) - Jafari Nedoushan, Reza; An, Yongsan; Yu, Woong-Ryeol; Abghary, Mohammad Javad
Abstract: Cellular auxetic materials possess a negative Poisson's ratio (NPR) and attractive mechanical properties; however, these materials are limited by their low stiffness and strength and strong anisotropy. To address these issues, we developed a novel auxetic honeycomb with a fully triangular architecture inspired by the anti-tetra chiral configuration. The new stretch-dominant structure was fabricated using a three-dimensional printing process. The resulting deformation behavior of the triangular auxetic honeycomb structure was compared with that predicted from finite element (FE) simulations; these revealed an NPR and high stiffness, in which the ratio of specific stiffness to specific density was 0.12. The simulations allowed for an NPR in both the longitudinal and transverse directions concurrently. Based on the mechanism revealed by the FE simulations, the novel triangular honeycomb can be tuned to have the same behavior in two orthogonal directions, while retaining high stiffness and an NPR.